Partial crack closure under block loading - Borrego, L. P. (2008)
Fatigue crack propagation tests under high-low and low-high block loading sequences have been performed in aluminium alloy specimens. The tests were carried out at constant [Delta]K conditions. Two stress ratios were analysed: R = 0.05 and R = 0.4. Crack closure was monitored in all tests by the compliance technique using a pin microgauge. The observed transient post load step behaviour is discussed in terms of the load change magnitude, [Delta]K baseline levels and stress ratio. The crack closure level was obtained and compared with the crack growth transients. A good agreement between experimental and predicted crack growth rates is obtained when the partial crack closure effect is properly taken into account. Therefore, plasticity-induced crack closure plays an important role on the load interaction effects observed in aluminium alloys.